Silenced voices unmasked stories of women weavers as preserver of culture. - Gultimo, Lalaine Isabel C. (2016.)
The study captured the stories of women weavers of Brgy. Indag-an, Miagao, Iloilo as agents of the maintenance and preservation of their cultural heritage, using the lens of Feminist Experiential Research Perspective. Grounding from the qualitative data gathered through narrative interviews and analyzed through the process of narrative analysis, results showed a comparison of reminiscences across life transitions of women weavers which were referred to as the collective trajectories. Moreover, the operative theories revealed life realizations of women weavers pertaining to their roles as preserver of culture. looking at it in a larger sacle, women were able to preserve weaving but at the same time, weaving has actually also preserved the women weavers culturally, financially and psychologically. Grounding on the findings, the researcher generated insights thay may contribute to the disclosure on gender studies. also, the utility of feminist Experiential Research Perspective and Narrative Psychology were recommended for further research on this topic.
Research Paper (Undergraduate, Bachelor of Arts in Psychology-Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Women weavers -- Miagao, Iloilo